2018
DOI: 10.1111/jdv.15350
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to omalizumab and relapse in chronic spontaneous urticaria: a study of 470 patients

Abstract: Background Chronic spontaneous urticaria (CSU) is defined as spontaneous occurrence of wheals and/or angioedema for ≥6 weeks. Omalizumab is a monoclonal anti-IgE antibody effective in refractory CSU, but its mechanism of action and markers predictive of response remain not completely defined.Objectives To correlate baseline levels of two proposed biomarkers, total IgE (bIgE) and D-dimer (bD-dimer), and clinical parameters to omalizumab response and to relapses after drug withdrawal.Methods In this retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
82
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 42 publications
16
82
1
6
Order By: Relevance
“…(15) Low baseline IgE has been described as a marker of poor response. (27,34,37) However this has not been confirmed by all studies. (38,39) Interestingly, a recent paper suggest that total IgE levels can be used as predictors of response to omalizumab only in nonatopic CSU patients, actually they showed that the atopic status modify the ability of IgE to predict the response to the treatment.…”
Section: F O R P U B B L I C a T mentioning
confidence: 79%
See 1 more Smart Citation
“…(15) Low baseline IgE has been described as a marker of poor response. (27,34,37) However this has not been confirmed by all studies. (38,39) Interestingly, a recent paper suggest that total IgE levels can be used as predictors of response to omalizumab only in nonatopic CSU patients, actually they showed that the atopic status modify the ability of IgE to predict the response to the treatment.…”
Section: F O R P U B B L I C a T mentioning
confidence: 79%
“…Furthermore, in line with previous reports, we found a significant decrease of D-dimer plasma levels under omalizumab treatment. Baseline D-dimer plasma levels do not predict the response to omalizumab, (27)(28)(29) with poor/no response and with slow response to omalizumab respectively. (27,(33)(34)(35)(36) Moreover, Schoepke et al put forward that autoimmune CSU have significantly lower total IgE serum levels than non-autoimmune CSU.…”
Section: F O R P U B B L I C a T mentioning
confidence: 87%
“…Rates of concomitant autoimmune diseases tend to be higher in type IIb [25,[118][119][120][121] Rates of concomitant allergic diseases might be higher in type I [119] Total IgE levels low in type IIb and normal or high in type I [14,25] Basopenia rates might be higher in type IIb [24, 111] 2 Eosinopenia rates tend to be higher in type IIb [122] C-reactive protein levels may be higher in type IIb [25,123] ANA positivity rates may be higher in type IIb [124] Responder rates to sgAHs may be lower in type IIb [122][123][124][125] Responder rates to omalizumab high in type I [28] and low in type IIb [62,122,126] Speed of response to omalizumab slow in type IIb [127] Immunosuppressive therapy can be effective in type IIb [128-134] 3 TPO, thyroperoxidase; TG, thyroglobulin; TF, tissue factor; IL, interleukin; dsDNA, double-stranded DNA; BHRA, basophil histamine release assay; BAT, basophil activation test; ASST, autologous serum skin test; WB, Western blot; ELISA, enzyme-linked immunosorbent assay; CRP, C-reactive protein; ANA, antinuclear antibodies; sgAHs, second-generation antihistamines. 1 Measured by ELISA or radioimmunoassay.…”
Section: Type I and Type Iib Autoimmunity: Emerging Endotypes Of Chromentioning
confidence: 99%
“…Straesser and co-authors stated that low serum IgE (15.2 IU/ml) in patients with chronic urticaria correlated with significantly lower omalizumab treatment response, underlined the importance of biomarkers in predict the patient response to treatment (12). Moreover, Marzano et al supported the hypothesis that CSU duration before omalizumab and baseline UAS7 may be clinical markers of relapse risk (13). Tharp and colleagues, analyzing available data from literature and real-life experiences, found that benefits and safety of omalizumab in the real-world treatment of CIU meet or exceed results gleaned from clinical trials, helping to inform both clinical treatment expectations and policy decisionmaking (14).…”
Section: Editorialmentioning
confidence: 96%
“…At present, experience from daily clinical practice suggests that some issues are still to be faced for optimal use of omalizumab in patients with CSU who have inadequate response to H1-antihistamines. As an example, management of re-treatment, long-term therapy, use of omalizumab during concurrent immunomodulatory therapy, and criteria to predict response to omalizumab treatment were recently discussed in the literature (8)(9)(10)(11)(12)(13)(14). Twenty-five CSU patients treated with 300 mg/month omalizumab (median duration ¼ 6 months) were retrospectively analysed.…”
Section: Editorialmentioning
confidence: 99%